Persepsi Guru Dan Siswa Tentang Proses Pembelajaran Online Dalam Mata Pelajaran Biologi di SMA Negeri 1 Luwuk - Moh. Fahri Haruna; Nurlia Nurlia; Sumarni Laruba; Abdul Muin Kenta (Universitas Muhammadiyah Luwuk, 2022)
Online learning is currently considered a new paradigm in teaching and learning activities where in the process of teaching and learning activities there is no need to be present in the class room. To find out the situation in the online learning process, it is necessary to have the perception so responses from teachers and students to the online learning process. This study aims' to determine teachers’ perceptions about the online learning process in biology subjects at SMA Negeri 1 Luwuk, and students’ perceptions about the online learning process in biology subjects at SMA Negeri 1 Luwuk. This is a descriptive qualitative research. The study population was 4 biology teachers and 214 students and the sample size was 2 biology teachers and 67 students. Data collection techniques used are interviews and instruments. Data were analyzed by useng descriptive qualitative methods. The results showed there are still many obstacles faced by teachers that result in the online learning procesa not running effectively so that teachers need support fromall parties so tha ty the online learning procces can be carried out properly and students preceptions about the online learning process in biology are very good. Keyboard: Online Learning, Perceptions, Biology Lessons